EVALUATION OF RELATED FACTORS AND OUTCOME IN FULL- TERM PREGNANCY WOMAN WITH PREVIOUS C-SECTION AT HAU GIANG OBSTETRICS AND PEDIATRICS HOSPITAL. (Vietnam Journal of Community Medicine, 2024)
Objective: (1) Determine the rate of cesarean section and vaginal birth in pregnant women with old cesarean section at Hau Giang Obstetrics and Pediatrics Hospital; (2) Survey some factors related to indications for cesarean section and vaginal birth in the above subjects.Research subjects and methods: cross-sectional descriptive study on 100 pregnant women with old cesarean section treated at Hau Giang Provincial Obstetrics and Pediatrics Hospital.Results: Caesarean section is the most commonly performed method with a rate of 96%, including elective surgery 52% and emergency surgery 44%. There are many factors related to the indication of birth method, including: history of previous vaginal birth (p = 0.002; 95% CI), cervical dilatation at the beginning of labor (p < 0.001, 95% CI), amniotic state at the beginning of labor (p < 0.001, 95% CI), old surgical wound pain (p = 0.003; 95% CI). The average hospital stay of pregnant women with old cesarean section is (6,16 ± 0,8 days). Vaginal birth had the shortest time (5 ± 1,4 days), followed by the emergency surgery group (6,05 ± 0,75 days) and the proactive surgery group (6,34 ± 0,71 days). The choice of birth method is related to the number of days in hospital (p=002, 95% CI).Conclusion: In most cases, cesarean section after an old incision is chosen over vaginal birth. There are many factors related to the method of birth, including: history of previous vaginal birth, previous surgical wound pain, amniotic fluid status, and cervical dilatation at the beginning of labor. The method of birth is related to the number of days in the hospital. The vaginal delivery group had a shorter hospital stay and lower treatment costs than the cesarean section group.
Keywords: Previous cesarean section, vaginal birth after cesarean section, treatment results, related factors.